SOME ASPECTS OF THE METHODOLOGY OF TEACHING RUSSIAN LANGUAGE AND LITERATURE (Academia Science Repository, 2023)
The methodology of teaching the Russian language begins with the teaching of the language of students of the beginning classes. The first method of learning the Russian language is this technique. Psychological-pedagogic zakonomernosti of the process of learning is the needs of society. The method of teaching the Russian language consists of literary parts of the language skills of students, the understanding of grammatics, changes in the language system in time (assimilatation) and other parts of the language language.